Analisis Makna dan Fungsi Tawar Pengobatan Suku Kutai pada Masyarakat Muara Muntai Kutai Kartanegara - Mahmudah Mahmudah; Nurdin Nurdin (Lembaga Yasin AlSys, 2026)
Although tawar pengobatan remains alive and practiced by the Kutai ethnic community in Muara Muntai, Kutai Kartanegara, studies that specifically discuss its meaning and function as an oral tradition of traditional healing remain limited. This study aims to describe the meaning and function of tawar pengobatan in the life of the Muara Muntai community. This study used a descriptive qualitative method. Data were collected through observation, interviews, recording, and documentation involving tawar reciters and community members who had been involved in this healing practice. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that tawar pengobatan has a distinctive speech structure, characterized by the use of symbolic language, repetition, and strong magical and spiritual elements. In terms of meaning, this tradition contains an explicit meaning in the form of a request for the patient’s recovery, while its implicit meaning reflects the community’s belief in the power of prayer, harmonious relations between humans and nature, and respect for ancestral heritage. In terms of function, tawar pengobatan serves as a means of healing, protection, strengthening religious values, binding social solidarity, and affirming the cultural identity of the Kutai community. The conclusion of this study affirms that tawar pengobatan functions not only as a traditional healing practice but also as a medium for transmitting cultural, spiritual, and social values that are important for the continuity of the identity of the Muara Muntai community. These findings imply the importance of documenting, preserving, and transmitting local oral traditions so that they remain relevant for future generations.